An overview of photocatalysis phenomena applied to NOx abatement - Joana Ângelo (2013)
This review provides a short introduction to photocatalysis technology in terms of the present environmental remediation paradigm and, in particular, NOx photoabatement. The fundamentals of photoelectrochemical devices and the photocatalysis phenomena are reviewed, highlighting the main reaction mechanisms. The critical historical developments on heterogeneous photocatalysis are briefly discussed, giving particular emphasis to the pioneer works in this field. The third part of this work focus mainly on NOx removal technology considering topics such as: TiO2 photochemistry; effect of the operating conditions on the photocatalysis process; LangmuireHinshelwood modeling; TiO2 photocatalytic immobilization approaches; and their applications. The last section of the paper presents the main conclusions and perspectives on the opportunities related to this technology.